A Cross-Sectional Study on the Cross-Talk of the COVID-19-Related Degree of Loneliness and the Etiological Factors Among the Elderly in Central China - Ju, Jie; Qi, Wen-bo; Zhang, Jia; Cao, Zhi-Jun; Tsai, Chi-Lun; Liu, Peng (Frontiers in Psychiatry, 2022)
Background The outbreak of COVID-19 has undoubtedly influenced the normal lifestyle of people worldwide, including the Chinese population. This study attempted to do supplementary research to the current situation of loneliness as well as the related risk factors among the elderly in the province in central Chinese during the COVID-19. Methods We conducted a cross-sectional study in one of the central Chinese provinces (Henan Province) from December 2020 to March 2021 using a multistage sampling method, and 568 elderly people without cognitive impairment were interviewed. The UCLA Loneliness Scale, Pittsburgh Sleep Quality Index (PSQI), Physical Activity Rating Scale (PARS-3), and Quality of Life Questionnaire SF-36 were adopted to collect information. We used univariate and multivariate logistic regressions to analyze the factors resulting in severe loneliness among the elderly with seldom or regular participation in physical exercises. Results During the epidemic in central China, the elderly suffering from loneliness syndrome accounted for 34.2%, of which 15.5% were severely lonely. Risk factors for severe loneliness were quality of life (OR: 7.129), sleep quality (OR: 3.778), seldom exercise (OR: 4.170), poor economic status (OR: 1.769), and negative attitude toward the prospects for the epidemic control (OR: 4.033). By grouping the participants in terms of physical activity, we found that the quality of life (OR:5.778) was a significant risk factor than sleep quality (OR:2.939) in the seldom exercise group, while the only risk factor in the regular exercise group was the quality of life (OR: 5.021). Conclusion There was an increase in the degree of loneliness among the elderly during the epidemic, and physical activity played an active role in relieving the severe loneliness of the elderly. Therefore, for the sake of the elderly, regular participation in physical exercises should be encouraged during the duration of the epidemic.